Two Methods for the Evaluation of Six Disinfectants Using Pseudomonas Aeruginosa and Serratia Marcescens as the Test Organisms - Yahya R. Faydi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
A total of 50 isolates of Pseudomonas aeruginosa and 6 isolates of Serratia Marcescens from various clinical specimens were used in this study. The action of various commercial disinfectants on these isolates was studied using the agar and broth dilution methods. All S. Marcescens strains were inhibited by. 0.15% 0-syl or 0.44% Savlon. While P. aeruginosa strains were inhibited by 0.3% 0-syl or 0.88% Savlon. Both organisms were inhibited by 0.65% Westaspet, 0.125% Phenol, 0.5% Acriflavin or 0.25% Micro - Bac.